2020
DOI: 10.3892/etm.2020.8884
|View full text |Cite
|
Sign up to set email alerts
|

Use of the modified Glasgow Coma Scale score to guide sequential invasive‑noninvasive mechanical ventilation weaning in patients with AECOPD and respiratory failure

Abstract: Sequential invasive-noninvasive ventilation (NIV) improves the outcomes of patients with respiratory failure caused by acute exacerbation of chronic obstructive pulmonary disease (AECOPD); however, there is no clear consensus on the optimal timing of the switch to sequential invasive-NIV in these patients. In the present study, a potential role for the modified Glasgow Coma Scale (GCS) score to guide sequential weaning was investigated. Patients with AECOPD and respiratory failure were prospectively recruited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
(37 reference statements)
1
6
0
Order By: Relevance
“…Similar to the previous study and our clinical experience, we also found age ( 21 , 22 ), Glasgow score ( 23 ), respiratory rate ( 24 ), oxygen saturation ( 25 ), serum potassium, PCO 2 , peripheral vascular disease, renal disease, diabetes mellitus, comorbidity index ( 26 ), SOFA score ( 27 ) were also associated with in-hospital mortality.…”
Section: Discussionsupporting
confidence: 89%
“…Similar to the previous study and our clinical experience, we also found age ( 21 , 22 ), Glasgow score ( 23 ), respiratory rate ( 24 ), oxygen saturation ( 25 ), serum potassium, PCO 2 , peripheral vascular disease, renal disease, diabetes mellitus, comorbidity index ( 26 ), SOFA score ( 27 ) were also associated with in-hospital mortality.…”
Section: Discussionsupporting
confidence: 89%
“…The results were in concurrence with the previous result. Excessive use of sedation and analgesia in the process of mechanical ventilation is the possible reason for delirium[ 22 ]. However, progressive early rehabilitation training mode was vital for patients rehabilitation training, especially when the patients were in disturbance of consciousness or ambiguity.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the use of a unidirectional valve is indicated to measure the MIP. Discussion about the best protocol has continued, and although some authors consider 20 seconds to be long enough, others argue that 40 to 60 seconds of unidirectional valve occlusion are required for MIP measurement [ 9 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the patient demographics and diagnoses, level of consciousness was assessed using a modified GCS reported in other studies [ 16 , 17 ] to assess motor, eye, and verbal responsiveness. The previous studies reported that the verbal component of the GCS can be omitted (because the participants were on MV) without compromising the reliability of the score.…”
Section: Methodsmentioning
confidence: 99%